Purification and properties of 5,10-methenyltetrahydromethanopterin cyclohydrolase from Methanosarcina barkeri. - te Brömmelstroet, B W (1990)
The 5,10-methenyltetrahydromethanopterin cyclohydrolase from Methanosarcina barkeri was purified 313-fold to a specific activity of 470 mumol min-1 mg-1 at 37 degrees C and pH 7.8. At this stage, the enzyme was pure as judged from polyacrylamide gel electrophoresis. The monofunctional enzyme was oxygen stable, but the presence of a detergent proved to be essential for its stability. Like the cyclohydrolase purified from Methanobacterium thermoautotrophicum (A. A. Dimarco, M. I. Donnelly, and R. S. Wolfe, J. Bacteriol. 168:1372-1377, 1986), the protein showed an apparent Mr of 82,000, and it is composed of two identical subunits as was concluded from nondenaturating and denaturating polyacrylamide gel electrophoresis. The enzymes from M. thermoautotrophicum and M. barkeri markedly differ with respect to the hydrolysis product of 5,10-methenyltetrahydromethanopterin: 5-formyl- and 10-formyltetrahydromethanopterin, respectively. The apparent Km for 5,10-methenyltetrahydromethanopterin was 0.57 mM at 37 degrees C and pH 7.8.